ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Tansa Amelia Syahputri; Yuyu Yuliati; Dede Salim Nahdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Scientific literacy is an important ability that needs to be developed among elementary school students to understand scientific phenomena and solve problems in everyday life. However, students’ scientific literacy remains a challenge, requiring learning models that can encourage active engagement and scientific thinking skills. This study aims to analyze the implementation of the Problem Based Learning (PBL) model on elementary school students’ scientific literacy through a Systematic Literature Review (SLR) approach. The research method follows the PRISMA 2020 guidelines by conducting the identification, selection, evaluation, and synthesis of relevant scientific articles. A total of 15 articles were analyzed based on research characteristics and the contribution of PBL implementation to scientific literacy. The results indicate that previous studies are predominantly quantitative research using experimental and quasi-experimental designs. The implementation of PBL provides a positive contribution to improving scientific literacy through problem-solving activities, scientific investigations, and contextual learning. Therefore, PBL can be considered an effective alternative learning model for developing scientific literacy skills among elementary school students.